Biochemical Tests as an Indicator for the Effects of Electrical Generator Exhausts on Human Health - Ali, Inaam Noori; Jawad, Hayder G.; Mohammad, Rahafat R. (Iraqi Journal of Science, 2022)
Diesel generators are used in various locations throughout Baghdad city, central Iraq, when the public electricity power is in outage. The main purpose of the current research is to investigate possible changes in certain biochemical parameters in the blood of operators of diesel generators in different locations Baghdad city, at both Rusafa and Karkh sides. The workers were divided according to the number of working years. Serum urea, creatinine, alkaline phosphatase (AlP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), albumin, total serum bilirubin (TSB), and glomerular filtration rate (GFR) were analyzed in samples from forty workers and compared with ten healthy persons as a control group. The findings revealed a substantial reduction in the amounts of creatinine and albumininine (p <0.01 (and the value of GFR, while the levels of AlP, AST, ALT, and TSB recorded a significant increase in the sera of the workers compared with the control group. Differences in the serum levels of urea were statically insignificant. The temporal analysis also showed that the continuous work in the generators’ locations for many years causes disorders in the biochemical parameters in the blood of workers.